Petrarca tra letteratura e potere politico - Špička, Jiří (Incontri. Rivista europea di studi italiani, 2013)
Petrarch between Literature and Political Power Francesco Petrarca (Petrarch) was not only an outstanding poet and scholar of his age, but also an interesting example of a public intellectual ante litteram, at least he appears to be so from the writings he left to posterity. His works in Latin, in particular, provide a strong critical commentary on the political issues of his time and about civilisation and history in general. Petrarch loved to live close to the centers of power and to maintain good relationships with influential political personalities; nevertheless, he managed to avoid getting involved in practical political activity or being recruited as a secretary or courtier. Despite not being of noble birth, he succeeded in being accepted into the most prestigious social circles and, at the same time, maintained sufficient independence and freedom to dedicate his time to literature. In his works he tried to impose ancient Rome as a social model and Roman heroes as exemplars of individual qualities; he also tried to convince the political powers (especially the Italian maritime republics and the Roman Emperor) to re-establish Italian dominance, to as great an extent as possible, within the borders of the Roman Empire. Petrarch sought to quell the violence of Italian political life and restore the papacy to Rome, with the aim of opposing French power in Europe.